La farmacoutilizzazione delle statine nella pratica clinica: risultati di uno studio di popolazione condotto su database amministrativi e di medici di medicina generale - Di Martino, Mirko; Capone, Alessandro; Russo, Pierluigi; Degli Esposti, Luca; Ceccarelli, Pierluigi; Buda, Stefano; Degli Esposti, Ezio; Caprino, Luciano (Farmeconomia. Health economics and therapeutic pathways, 2003)
In spite of findings of large-scale clinical trials which showed an overall reduction of morbidity and mortality from coronary heart disease in patients treated with 3-hydroxy-3-metylglutaryl coenzyme-A reductase inhibitors (statins), relatively little is still known about the real prevalence of treatment in general practice setting, particularly in patients with a high cardiovascular risk. The objective of this study was to investigate among patients with cardiovascular risk profile estimated according to the Framingham Heart Prediction Risk Study, the percentage of those exposed to statins, and the proportion of patients reaching total cholesterol (TC) target levels. A cross-sectional analysis was conducted on a large cohort of patients listed in the administrative databases of the Local Health Unit of Ravenna (total resident population of 356,000). In 2001, every single patient who received a prescription for a statin, and/or with a recorded plasma TC level, and/or with a hospital admission for cardiovascular reasons (identified by ICD-9 code), and/or with a clinical appraisal based on the presence of cardiovascular risk factors, was defined eligible. Sebsequently, pharmaceutical, and nosocomial databases, were cross-linked with that of 50 general practitioners in order to assess the pharmacoutilization of statins on a patient-by-patient basis. A cohort of 9,208 patients with a well documented cardiovascular risk profile were analyzed. The mean age of those patients was 57 (SD=17) years and 42% of them was male. On the basis of raised TC levels and cardiovascular risk profiles, patients for whom a statin treatment was suggested amounted to 7,233. However, the number of those who received statins was significantly lower (n = 1,343), corresponding to 18.6%. In those exposed to statins, just a small group of patients reached a level of TC below 190 mg/dl (n = 271), equivalent to 20.2%. In the group of treated who did not achieve recommended TC target levels, 31.7% (n = 340) of patients was at very high cardiovascular risk. Moreover, among all patients with high plasma TC levels (n=5,890), there was a 45.7% (n = 2,690) who did not received any lipid lowering drug even though they had a high cardiovascular risk profile. Results from large population-based administrative databases suggest a remarkable level of undertreatment among patients with cardiovascular risk factors. Furthermore, many patients did not achieve recommended TC target levels with their statin treatment. Pharmacoutilization of statins in general practice reveals the need of a more careful pursuing of therapeutic goals.